ANALYSIS OF THE EFFECT OF CUSTOMER SATISFACTION ON PURCHASE DECISIONS AT COFFEESHOP"SELASA_COMMUNA" MEDAN - Ratu Aisyah Ratih Primaputri; Sirojuzilam; Iskandarini (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to analyze how far the relationship between customer satisfaction and purchasing decisions for customers of the selasa_communa coffee shop. In this study, purposive sampling with certain criteria amounted to 40 customers. The data collected uses a scale from customer satisfaction and purchasing decisions. Data were analyzed using simple regression analysis. The results showed a significant positive relationship between customer satisfaction and purchasing decisions for consumers at the selasa_communa coffee shop. In this study, customer satisfaction who have purchased at the selasa_communa coffee shop can be used as a stimulus for prospective customers in making purchasing decisions.